Pack of Applied Programs for Complex Analysis of Thermo-Compressors - S. V. Zditovetskaya; V. I. Volodin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper proposes a pack of applied programs intended for conjugate calculation of cycle parameters with heat exchangers of thermo-compressor loop and a calculation of irreversible losses in the loop binding including non-stationary operational  mode is added to the pack.The paper contains investigations of thermo-compressor operation in the system of forced and exhaust ventilation for reduction of heat consumption by a heater in the cold season of the year